On the relationship between the Mediterranean Oscillation and winter precipitation in the Southern Levant - Törnros, Tobias (Atmospheric science letters, 2013)
Empirical Orthogonal Function (EOF) analysis was applied to 25 homogenous precipitation series in the Southern Levant covering the years 1960-1993. The EOF-1 explained 60-71% of variance and exhibited a significant correlation with a particular Mediterranean Oscillation Index (MOI) in December-February. It is shown that winter precipitation is associated with positive MOI phases and Cyprus lows. By fitting gamma distributions to monthly precipitation; it could furthermore be shown that during negative MOI phases, the probability of above average winter precipitation is 22%. During positive MOI phases, the corresponding probability is much higher, at around 59%.